How local is hospital treatment? An exploratory analysis of public/private variation in location of treatment in Irish acute public hospitals - Jacqueline O'Reilly; Miriam M. Wiley (The Economic and Social Research Institute (ESRI), 2008)
This paper undertakes an exploratory examination of the factors that affect where patients receive treatment from Irish acute public hospitals, with particular regard to the influence of patients' public/private status. National univariate statistics indicate that private discharged patients are slightly more likely to be treated outside their county of residence than their public counterparts. A multivariate model necessarily estimated at the county level provides indirect support for this finding for the category of day patients, but not for planned and emergency in-patients. The effects of the other patient characteristics also varied across the three models, although there was consistency in the impact of supply-side factors, such as the type and availability of services. As there appears to be some tendency for private day patients to have a slightly greater propensity to travel for acute public hospital treatment, further research is required to identify the reasons for this, as well as the consequences for public and private patients resident in the source and destination counties.
Keywords: 330; Gesetzliche Krankenversicherung; Private Krankenversicherung; Krankheit; Krankenhaus; Dienstleistungsqualität; Irland